2016
DOI: 10.1016/j.path.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pancreatic Cyst Fluid

Abstract: Synopsis Pancreatic cysts are extremely common, and are identified in between 2% to 13% on abdominal imaging studies. The majority of pancreatic cysts are pseudocysts, serous cystic neoplasms (SCNs), mucinous cystic neoplasms (MCNs) or intraductal papillary mucinous neoplasm (IPMNs). The management of pancreatic cysts depends on whether a cyst is benign, has malignant potential, or harbors high-grade dysplasia or invasive carcinoma. The diagnosis of pancreatic cysts, and assessment of risk of malignant transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 38 publications
(44 reference statements)
0
28
0
5
Order By: Relevance
“…Low amylase levels can be useful in excluding a pseudocyst, as shown in a large meta-analysis which found that a cyst fluid amylase level of <250 IU/l had a very high specificity (98%) for excluding a pseudocyst [25]. In contrast, a high cyst fluid amylase level is not helpful, as it is found in multiple types of pancreatic cysts including SCAs, IPMNs, and MCNs [26]. Some authors have hypothesized that IPMNs, which have a communication between the main pancreatic duct and the cyst, would have a high cyst fluid amylase level, whereas MCNs, which have no connection with the main pancreatic duct, should have a low amylase level.…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…Low amylase levels can be useful in excluding a pseudocyst, as shown in a large meta-analysis which found that a cyst fluid amylase level of <250 IU/l had a very high specificity (98%) for excluding a pseudocyst [25]. In contrast, a high cyst fluid amylase level is not helpful, as it is found in multiple types of pancreatic cysts including SCAs, IPMNs, and MCNs [26]. Some authors have hypothesized that IPMNs, which have a communication between the main pancreatic duct and the cyst, would have a high cyst fluid amylase level, whereas MCNs, which have no connection with the main pancreatic duct, should have a low amylase level.…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) cystic fluid levels have limited accuracy and are not useful to confirm or rule out the presence of malignancy . Although molecular analyses are considered to be very promising, a truly accurate and reliable marker has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Although molecular analyses are considered to be very promising, a truly accurate and reliable marker has yet to be identified. Data on the use of needle‐based confocal laser endomicroscopy (CLE) are promising, even if better interobserver agreement and validation are needed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lesions collect pancreatic secretions, including pancreatic amylases and lipases. The identification of these enzymes inside the cysts allows an easy diagnosis (87). The lesions commonly originate as extensions from the diseased pancreas, but could also migrate to different sites of the retroperitoneal space (88).…”
Section: Discussionmentioning
confidence: 99%